Review of Juridic Inclusive Education for Autistic Children at SDN 024777 Binjai According to the Permendiknas RI Number 70 Year 2009 - Dina Andiza (Budapest International Research and Critics University, 2021)
Autism is a condition that affects a person from birth or during infancy, which makes him unable to form normal social relationships or communication. Inclusive education is an education system that provides opportunities for all children who have disabilities and have the potential for intelligence and/or special talents to participate in education or learning in an educational environment together with other students. This paper presents the concept of inclusive education from an epistemological perspective. In this study, the formulation of the problem is as follows: What is the right of every child with special needs (autism) to get a proper education according to Permendiknas Number 70 of 2009?; How is the implementation of inclusive education for children with special needs (autism) at SDN No. 024777 Binjai, In this study using a survey method with a qualitative approach. To obtain data, the researcher conducted direct interviews with parents of students (autistic) who are entitled to inclusive education, the Principal of SDN 024777 Binjai, Teacher of SDN 024777 Binjai, who saw the process of children going on until the child reached mature adulthood. To achieve this, every child has the right to a good education, including children with special needs. Employees of the Department of Education and Culture of Binjai City. The data analysis used in this research is triangulation analysis. Those who are different because of the disability, are ostracized, do not get a touch of affection and social contact which means that their existence is not even recognized. The government is amid inclusive education, where inclusive education can place all children (normal children and children with special needs) in a community which is an effort not to separate them from normal society. To provide a deeper understanding of the sources of inclusive education, this paper will present inclusive education in the world of Islamic Epistemology which is a branch of philosophy and examines the estuary of science in which inclusive education is found.